An optimization model for multi-type pallet allocation over a pallet pool - Jianwei Ren; Bo Liu; Zhengyu Wang (Advances in Mechanical Engineering, 2017)
Pallets are widely used around the world. Pallet pooling, as a useful management method of pallets, has become more and more popular. It is very important to allocate pallets over a pallet pool efficiently. However, there is very little literature on the pallet allocation problem as to our knowledge. This article addresses a pallet allocation problem where some uncertain parameters can be estimated through historical data, while some others cannot be. To address this problem, with the method of stochastic chance constrained programming and scenario planning, we propose an optimization model in which sustainable factors and customer priority factors are taken into account. The sustainable factors are used to measure the sustainable development costs of pallets. The customer priority factors are used to measure the customers’ rating. It is proved by experimental tests that the model can help pallet pool managers make more effective pallet allocation schemes against uncertainty. It is also suggested by the results that we should pay attention to sustainable factors and customer priority factors when making decisions.